DetecciÃ³n oportuna de cÃ¡ncer de prÃ³stata en los mÃ©dicos de primer contacto en MÃ©xico: estudio transversal - Mario J. Basulto-MartÃnez; Jorge E. Ojeda-PÃ©rez; IvÃ¡n A. Velueta-MartÃnez; Guillermo J. Cueto-Vega; Juan P. Flores-Tapia; Ma del Refugio GonzÃ¡lez-Losa (Permanyer, 2021)
Aim: This study aims to assess primary care physicians (PCPs) knowledge and skills regarding prostate cancer early detection (PCa-ED). Materials and methods: A survey about knowledge and skills of PCa-ED was delivered to PCP. Logistic regression analysis was conducted for the propensity of PCP to test prostatic specific antigen (PSA) on asymptomatic men. Results: The survey was completed by 170 PCP. Score on risk factors knowledge was 51.5 ± 15.7% a better score was not associated with conducting PCa-ED (p = 0.674). The 40.6% answered having an institutional program on PCa-ED and 86% having access to PSA testing. Testing PSA on asymptomatic men was found in 40%. Moreover, 61.2% do not performed any digital rectal examination for PCa-ED, and this was not associated with preventing factors such as lack of space, time, and assistance (p > 0.05). Fewer years in practice and being a family medicine resident were associated with a less likelihood of testing PSA in asymptomatic men. The only associated factor in the multivariable model was having access to PSA testing (odds ratio: 3.36 confidence interval 95% 1.54-7.30) p = 0.002). Conclusions: A low rate of PCP performs PCa-ED and using concepts outside evidence-based recommendations. A national program on PCa-ED and continuing medical education for PCP are a promising strategy to improve PCa-ED.